Combinatorial optimization and applications : 11th International Conference, COCOA 2017, Shanghai, China, December 16-18, 2017, Proceedings, Part I /: 11th International Conference, COCOA 2017, Shanghai, China, December 16-18, 2017, Proceedings, Part I. (2017) - Unknown
No abstract available